Macroeconomic Determinants of Economic Growth in Pakistan (The Pakistan Development Review, 1998)
The main purpose of this paper has been to examine the effects of some of the key macroeconomic variables on Pakistan’s economic growth. Multiple regression framework is used to separate out the effects of key macroeconomic factors on growth over the period 1959-60 to 1996-97. The quantitative evidence shows that primary education to be an important prerequisite for accelerating growth. Similarly, increasing the stock of physical capital would help to contribute to growth. The empirical results also suggest that openness of Pakistan’s economy promotes economic growth. Alternatively, the budget deficit is negatively related to both output growth variables. The external debt is also negatively related to growth, suggesting that relying on domestic resources is the best alternative to finance growth. However, the results presented in this study reinforce the importance of sensible long-run growth-oriented policies to obtain sustainable growth.